2021
DOI: 10.1088/1755-1315/893/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in WRF model prediction for heavy rain events over North Sumatra region using satellite data assimilation

Abstract: Located adjacent to the Indian Ocean and the Malacca Strait as a source of water vapour, and traversed by the Barisan Mountains which raise the air orographically causing high diurnal convective activity over the North Sumatra region. The convective system that was formed can cause heavy rainfall over a large area. Weather Research and Forecasting (WRF) was a numerical weather model used to make objective weather forecasts. To improve the weather forecasts accuracy, especially for predict heavy rain events, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The average accuracy of forecasts for daily rainfall from 2014-2017 varies from 85% to 82%. The correlation coefficient is best in the rainy season and the lowest RMSE value occurs in the dry season [4].…”
Section: Introductionmentioning
confidence: 95%
“…The average accuracy of forecasts for daily rainfall from 2014-2017 varies from 85% to 82%. The correlation coefficient is best in the rainy season and the lowest RMSE value occurs in the dry season [4].…”
Section: Introductionmentioning
confidence: 95%
“…In Indonesia, [13], [14], [15], [16], [17], [18], [19], and [20] have also conducted the same study. Especially for the island of Sumatra, [21], [22], [23], and [24] showed that GPM IMERG is one of the possible rainfall satellite data that can be used in imitating the ground station data.…”
Section: Introductionmentioning
confidence: 99%